2010
DOI: 10.5194/acp-10-8025-2010
|View full text |Cite
|
Sign up to set email alerts
|

Climatology and comparison of ozone from ENVISAT/GOMOS and SHADOZ/balloon-sonde observations in the southern tropics

Abstract: Abstract. In this paper, the stellar occultation instrument GOMOS is compared with ozonesondes from the SHADOZ network. We only used nighttime O 3 profiles and selected 8 Southern Hemisphere stations. 7 years of GOMOS datasets (GOPR 6.0cf and IPF 5.0) and 11 years of balloon-sondes are used in this study. A monthly distribution of GOMOS O 3 mixing ratios was performed in the upper-troposphere and in the stratosphere (15-50 km). A comparison with SHADOZ was made in the altitude range between 15 km and 30 km.In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Meijer et al (2004) but on a significantly larger dataset and found large GOMOS positive bias, over 40 %, in the tropical UTLS and below. This conclusion is in full agreement with the validation work of Mze et al (2010) using ozone soundings from eight SHADOZ stations. The validation studies performed so far (which are also focused mainly on the stratospheric ozone) indicate, however, the presence of large GOMOS ozone bias in UTLS also in IPF v6 data.…”
supporting
confidence: 80%
“…Meijer et al (2004) but on a significantly larger dataset and found large GOMOS positive bias, over 40 %, in the tropical UTLS and below. This conclusion is in full agreement with the validation work of Mze et al (2010) using ozone soundings from eight SHADOZ stations. The validation studies performed so far (which are also focused mainly on the stratospheric ozone) indicate, however, the presence of large GOMOS ozone bias in UTLS also in IPF v6 data.…”
supporting
confidence: 80%
“…Lidar has a better vertical resolution mainly in the lower stratosphere, but is limited to the lower part (15-45 km). This section does not intend to present a large scale validation of GOMOS using a larger set of instruments as this is covered by other publications (e.g., Meijer et al, 2004;Mze et al, 2010;van Gijsel et al, 2010). Here the main objective consists of assessing the long-term evolution and confirming the validity of the tests presented previously in Sect.…”
Section: Data Comparisonsmentioning
confidence: 99%
“…While the frequency, seasonality, and impacts of STT events have been well described in the tropics and Northern Hemisphere (NH), observational estimates from the SH extratropics are noticeably absent in the literature. The role of STT in the SH remains highly uncertain due to the more limited data availability compared to the NH and the temporal sparsity of these datasets (Mze et al, 2010;Thompson et al, 2014;Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%